Physical Activity Levels and Perceived Changes in the Context of Intra-EEA Migration: A Study on Italian Immigrants in Norway - Calogiuri, Giovanna; Rossi, Alessio; Terragni, Laura (Frontiers in Public Health, 2021)
As mobility within the European Economic Area (EEA) is on the rise, it is important to understand migrants’ health-related behaviours (such as physical activity [PA]) within this context. This study investigated the PA profile of Italian immigrants in Norway as compared with the general Norwegian population’s, and the extent to which it varies in relation to key sociodemographic characteristics. The data were retrieved from the Mens Sana in Corpore Sano study. In order to enhance the sample’s representativeness, the original dataset (n = 321) was oversampled in accordance with the proportion of key sociodemographic characteristics of the reference population using the ADASYN method (resampled n = 531). The instruments, which included measurements of PA behaviour and key sociodemographic characteristics (gender, age, region of residence, and educational level), were developed to allow direct comparisons with existing surveys in the Norwegian population. The results indicate that a large majority of Italian immigrants perceived they were as or even more physically active in Norway than they would have been if they continued living in Italy, while 20% of the Italians perceived instead a negative impact on their PA habits. No significant differences were found in the PA levels of the Italians in comparison with the Norwegian population, though some differences were found in relation to specific modes of PA. After controlling for multiple sociodemographic characteristics, men, those with lower educational levels and, to a certain extent, older adults tended to perceive a more negative impact and be less physically active than their respective counterparts. Compared with those living in the most urbanized regions, a larger proportion of those living in less urbanized regions perceived a negative impact, though no differences were observed in terms of PA levels. The findings are discussed in light of acculturation, gender, and social gradients. This knowledge sheds light on important health-related behaviours among Italians in Norway, which can inform initiatives that aim at promoting PA in this specific group as well as other similar contexts of intra-EEA migration.